Influence of rarefaction on the computation of aerodynamic parameters in hypersonic flow - Zuppardi, G; Paterna, D (Proceedings of the Institution of Mechanical Engineers. Part G, Journal of aerospace engineering, 2002)
Abstract The results from two well-known and widely accepted codes, the Navier—Stokes solver FLUENT and the direct simulation Monte Carlo (DSMC) solver DS2G, have been analysed in order to fix the levels of the flow field rarefaction where the codes can work properly for the computation of aerodynamic forces and heat flux on a spacecraft during the re-entry. This subject has already been widely investigated; thus the purpose of the present work is to provide a further contribution. In order to make realistic computations, a probable path of a typical capsule, returning from an interplanetary mission to Earth, has been considered in the altitude range 50—120 km. Proper use of FLUENT was fixed at the free-stream Knudsen number Kn∞ < 7×10−5. Attempts have been made to increase this limit, but with no success. More specifically, a finer mesh as well as a slip velocity and temperature jump were considered. Physical conditions like the lack of isotropy of the pressure tensor and the failure of the classical phenomenological equations, both increasing with the rarefaction, are very probably the causes of the failure of FLU EN T. The basic principle of the DSMC solver is valid at each rarefaction level; a sensitivity analysis on the characteristic dimension of the cell, on the time step and on the number of simulated molecules verified that the restrictions on DS2G are imposed only by the capability of the computer. As neither experimental data nor numerical results are available at the present test conditions, the evaluation of the results relies just on qualitative considerations about the trends of experimental data, reported in the literature, of a sphere in a hypersonic transitional regime.